Insensitivity of Human iPS Cells-Derived Mesenchymal Stem Cells to Interferon-γ-induced HLA Expression Potentiates Repair Efficiency of Hind Limb Ischemia in Immune Humanized NOD Scid Gamma Mice. (6th August 2015) - Sun, Yue-Qi; Zhang, Yuelin; Li, Xin; Deng, Meng-Xia; Gao, Wen-Xiang; Yao, Yin; Chiu, Sin-Ming; Liang, Xiaoting; Gao, Fei; Chan, Camie W.; Tse, Hung-Fat; Shi, Jianbo; et al.
Abstract: Adult mesenchymal stem cells (MSCs) are immunoprivileged cells due to the low expression of major histocompatibility complex (MHC) II molecules. However, the expression of MHC molecules in human-induced pluripotent stem cells (iPSCs)-derived MSCs has not been investigated. Here, we examined the expression of human leukocyte antigen (HLA) in human MSCs derived from iPSCs, fetuses, and adult bone marrow (BM) after stimulation with interferon-γ (IFN-γ), compared their repair efficacy, cell retention, inflammation, and HLA II expression in immune humanized NOD Scid gamma (NSG) mice of hind limb ischemia. In the absence of IFN-γ stimulation, HLA-II was expressed only in BM-MSCs after 7 days. Two and seven days after stimulation, high levels of HLA-II were observed in BM-MSCs, intermediate levels were found in fetal-MSCs, and very low levels in iPSC-MSCs. The levels of p-STAT1, interferon regulatory factor 1, and class II transactivator exhibited similar phenomena. Moreover, p-STAT1 antagonist significantly reversed the high expression of HLA-II in BM-MSCs. Compared to adult BM-MSCs, transplanting iPSC-MSCs into hu-PBMNC NSG mice revealed markedly more survival iPSC-MSCs, less inflammatory cell accumulations, and better recovery of hind limb ischemia. The expression of HLA-II in MSCs in the ischemia limbs was detected in BM-MSCs group but not in iPSC-MSCs group at 7 and 21 days after transplantation. Our results demonstrate that, compared to adult MSCs, human iPSC-MSCs are insensitive to proinflammatory IFN-γ-induced HLA-II expression and iPSC-MSCs have a stronger immune privilege after transplantation. It may attribute to a better therapeutic efficacy in allogeneic transplantation. Stem Cells 2015;33:3452–3467